2021
DOI: 10.3390/cancers13225771
|View full text |Cite
|
Sign up to set email alerts
|

Her2-Positive Cancers and Antibody-Based Treatment: State of the Art and Future Developments

Abstract: HER2 positive breast cancer represent about 20% of all breast cancer subtypes and it was considered the subtype with the worst prognosis until the discovery of therapies directed against the HER2 protein. The determination of the status of the HER2 must be very precise and well managed to identify this subtype, and there are very specific and updated guides that allow its characterization to be adjusted. Treatment in local disease has been considerably improved with less aggressive and highly effective approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Disappointingly, clinical trials have also not yet demonstrated a synergistic effect of immunotherapy and HER2-targeting agents. Studies examining the potential of immune checkpoint inhibitors in metastatic HER2-positive BC patients have yielded low anti-tumour efficacy in unselected, heavily pretreated patients, with limited activity mostly being seen in PD-L1-positive tumours 29 31 . The early stages of cancer, which is usually confined to the breast, involve a less invasive tumour and a more permissive microenvironment allowing the immune system to recognise and respond to tumour antigens.…”
Section: Methodsmentioning
confidence: 99%
“…Disappointingly, clinical trials have also not yet demonstrated a synergistic effect of immunotherapy and HER2-targeting agents. Studies examining the potential of immune checkpoint inhibitors in metastatic HER2-positive BC patients have yielded low anti-tumour efficacy in unselected, heavily pretreated patients, with limited activity mostly being seen in PD-L1-positive tumours 29 31 . The early stages of cancer, which is usually confined to the breast, involve a less invasive tumour and a more permissive microenvironment allowing the immune system to recognise and respond to tumour antigens.…”
Section: Methodsmentioning
confidence: 99%
“…1 In the hormone receptor-positive (HR1)/HER21 subpopulation in the KRISTINE trial, neoadjuvant T-DM1 1 pertuzumab and docetaxel 1 carboplatin 1 trastuzumab 1 pertuzumab led to comparable pCR rates (35.1% v 43.8%) and similar invasive disease-free survival (iDFS; hazard ratio [HR], 1.44 [95% CI, 0.54 to 3.88]). 2,3 No predictive markers for T-DM1 have been established so far; particularly, the impact of PIK3CA mutation remains unclear. 4,5 Moreover, several studies indicate that high HER2 expression (by mRNA and/or immunohistochemistry) associates with enhanced benefit from T-DM1.…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance is currently a major problem in several cancers such as UM (uveal melanoma), RCC (renal cell carcinoma), and HNSCC (head and neck squamous cell carcinoma). Although the 1980s was the decade of general radio-chemotherapy with the use of very toxic antitumor drugs and radiation procedures that resulted in numerous side effects, the 2000s was the decade of targeted therapies due to the development of treatments that specifically target driving mutations [ 23 , 24 , 25 ]. Despite the improvements, many of the patients were not cured and suffered relapses.…”
Section: Introductionmentioning
confidence: 99%